INNOVATIONS AND DIGITAL TRANSFORMATION - ECONOMIC GROWTH DRIVERS IN THE EUROPEAN UNION COUNTRIES - Šćepanović, Ivan; Stevanović, Mirjana; Šćepanović, Vesna (ACADEMIC REVIEW, 2025)
This paper deals with technological innovations and digital transformation in the IT sector of European Union (EU) countries. The focus is on the analysis of trends and the impact of technological innovation as well as digital transformation on economic growth, competitiveness and social progress within EU countries. In the first part of the paper, key aspects of innovation and digital transformation are outlined, including the role of technology startups, research centers and public-private partnerships. A systematic presentation of various support policies for digital transformation implemented by the European Commission (EC) and national member governments in the last 15 years is given. The second part of the paper is devoted to the identification of the challenges the sector faces in terms of innovation. These include issues related to digital security, data privacy, the lack of experts in the IT sector and the need for sustainable technological solutions.